Transposition of the Pterygopalatine Fossa during Endoscopic Endonasal Transpterygoid Approaches - Pinheiro-Neto, Carlos D.; Fernandez-Miranda, Juan C.; Prevedello, Daniel M.; Carrau, Ricardo L.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Introduction Complete or partial removal of the pterygoid process provides lateral extension of the endonasal corridor necessary to approach the Meckel cave, infrapetrous skull base, and medial infratemporal fossa. This paper provides the anatomical foundations for the endoscopic endonasal transpterygoid approach with preservation of all neurovascular structures inside the pterygopalatine fossa.Methods Eight endoscopic transpterygoid approaches were performed in fresh cadaveric specimens. In all dissections the vidian nerve and the periosteal sac enclosing the pterygopalatine fossa were preserved.Results We reliably transposed the pterygopalatine fossa to approach the Meckel cave, infrapetrous skull base, and medial infratemporal region, preserving the neurovascular structures inside the pterygopalatine fossa in all specimens.Conclusions The transposition of the pterygopalatine fossa neurovascular structures for endoscopic endonasal approaches to the skull base is an alternative technique that is both feasible and desirable. The transposition requires no additional technical skills but requires comprehensive knowledge of its anatomy. The anatomical preservation of the neurovascular structures is potentially beneficial to the quality of life of patients. Clinical studies are necessary to prove the real benefits of this technique.
Keywords: endoscopy; endonasal; cranial base; pterygopalatine fossa; transpterygoid approaches